Bridging the digital divide through the eLearning Centers Project. A collaboration amongst school, state and community - Abdullah@Mustafa, Anna Christina (2004)
This paper presents the expreriances of The eLearning Centers Project, a project initially mooted by the Basic Education Research Unit, the School of Educational Studies, Universiti Sains Malaysia to the Penang State Government as one of several efforts to realize the state's objective of achieving the vision of the k-economy and e-society in Penang. Launched officially in June 2003, the project has evolved and expanded as its potential to bridge the digital divide between the different socio-economic populations has been recognized. Hence, its focus now is more on providing access to eLearning opportunities to the rural and marginalized school-going children, with a mobile eLearning unit being includedas its new thrust in reaching out to these groups. The paper will describe how the project was promoted to various parties in the community to tap on their respective resources, be it time, expertise, service, hardware, software or even moral support so as to synergise the efforts of all interested parties to sustain the project and to ensure the achievement of its targets and objectives.